VIBRIO - BACTERIA - CONTROLLING POTENTIAL OF A SEDIMENT BIOELECTROCHEMICAL SYSTEM INTEGRATED IN A TEN-LITER-SCALED BRACKISH AQUACULTURE MODEL - AN INITIAL UPSCALE STUDY (Vietnam Journal of Agriculture and Environment, 2023)
Vibrio bacteria are among the most serious pathogens of aquatic creatures. Furthermore, they can cause diseases at any stage in the lifecycle of aquaculture animals with mortality up to 100%, which results in great economic losses. To control these agents, the currently widely-applied solution is to use antibiotics, which cause environmental pollution and drug resistance in microorganisms. Another solution is biological products, which have not yet been proven highly effective. In this context, there have been studies showing that a promising new solution is to use a sediment bioelectrochemical system (SBES) though only at small scales (